Desempenho térmico de blocos de vedação com uso de gesso e de resíduos poliméricos - Medeiros, Mellyne Palmeira (2016)
In lastest years, have been noticed the growth of social interest house in Brazil. However, the lower housing conditions and environmental degradation are characteristics of most of the produced housing. Financial constraints have been the main argument to justify these deficiencies. Seeking technical solutions, concerned with regard to environmental and economic issues for the construction sector, the use of gypsum is advantageous because it is less aggressive caking for the environment. Thus, this study aims to verify the changes in the physical and mechanical properties, and thermal performance of composite gypsum matrix with polymeric waste additions such as Ethylene Vinyl Acetate (EVA) and Expanded Polystyrene (EPS). The composite of gypsum and waste of EVA and EPS were used in the production of blocks for masonry sealing. It was also used bottles of PET (Poly Ethylene Terephthalate) inside of the produced blocks called in this work, GESSOPET. It has been found that the gypsum composite blocks of residues, both EVA as EPS showed better related to the thermal performance when compared with block without waste additions, manufactured only with plaster. Finally, this paper aims to contribute to the development of construction technologies using raw materials with low environmental impact and promote more economic construction.